2011
DOI: 10.1007/s11293-010-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

The Bank Failure Rate, Economic Conditions and Banking Statutes in the U.S., 1970–2009

Abstract: Bank failures, Economic factors, Financial factors, Banking legislation, G18, G20, G21,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…ROA is also a very popular measure to assess bank performance [28][29][30][31][32][33][34][35]. Other variables are bank failure rates [36,37], net interest margin [38], growth in loans [39], and probability of distress events [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…ROA is also a very popular measure to assess bank performance [28][29][30][31][32][33][34][35]. Other variables are bank failure rates [36,37], net interest margin [38], growth in loans [39], and probability of distress events [4].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies concluded that bank provisions increase with non-performing loans and strike at the bank capital, and as the sources of systemic risk. Some other studies applied bank's specific factors (CAMEL) as a measure of bank stability, the reviews are included Bongini et al (2001), Calomiris & Mason (2003b), and Cebula et al (2011). However, the drawback of using this measure is the CAMEL rating is not forward-looking and may not be good enough to track the emerging risk.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Given this context, the present study seeks to provide contemporary insights into factors that have systematically influenced bank failures in the USA over time. Although bank failure rates have been recently investigated, for example, by Cebula et al (2011), the present undertaking investigates this issue by estimating models that contain more financial/economic variables and more government banking statutes[1] than previously investigated and by adopting more robust econometric techniques[2] than most previous studies. In addition, this study examines more current data, allowing it to take the entire Great Recession and five years of additional data for the post-Great Recession experience into consideration.…”
Section: Introductionmentioning
confidence: 99%